Analisis Postur Pekerja Pada Proses Produksi Tahu Berdasarkan Metode Rapid Entire Body Assessment Di CV Lahan Faedah - Alif Fauza Dwi Prirasetyo; Nina Mahbubah (Jurnal Teknologi, 2021)
Musculoskeletal disorder is a problem for worker. The research purposes in the CV . Lahan Faedah are analysing working position can cause musculoskeletal disorder and give suggestions to the positions that need improvement. The REBA is extension of Rapid Entire Body assessment, which is a method that provides an objective measurement of the risk of MSDs caused by activity but only for the assessment of activities that have little movement and involve the whole body, namely by combining Table A and Table B to Table C. There are 3 positions The work analysed, namely Work Position A, B, C. The results of the three work positions using the REBA method are work position A, the soybean milling process gets a score of 9 with a high risk level, it is proposed that it requires corrective action to work posture or is given a tool so that the operator does not had a hard time getting the soybeans into the grinding machine